2010
DOI: 10.1007/s00535-010-0341-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of recurrence after curative resection for T1 colorectal cancer: Japanese multicenter study

Abstract: The recurrence rate after curative resection for node-negative T1 colorectal cancer was very low. The effectiveness of surveillance to detect recurrence after curative resection for T1 colorectal cancer should be validated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 37 publications
7
84
1
Order By: Relevance
“…(RR=1.33, 95% CI: 1.17-1.51; Fig. 3), which was consistent with the main results (4)(5)(6)11,12,(22)(23)(24).…”
Section: Sensitivity Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…(RR=1.33, 95% CI: 1.17-1.51; Fig. 3), which was consistent with the main results (4)(5)(6)11,12,(22)(23)(24).…”
Section: Sensitivity Analysissupporting
confidence: 80%
“…Stratification of patients according to the status of the muscularis mucosae (whether the muscle fibers were maintained or fragmented/disappeared), pathological factors and patient gender provides more appropriate indications for additional surgery along with lymph node dissection in this patient population, and may help reduce the incidence of unnecessary surgery. Several other studies also reported that the rate of LNM was higher in female compared with male patients (5,11), and that female gender was an independent risk factor for LNM in patients with T1 lower rectal cancer (23).…”
Section: Discussionmentioning
confidence: 95%
“…Nodal involvement is associated with an increased risk of local recurrence and shorter overall and disease-free survival time (18)(19)(20). Lymph node metastasis generally occurs in approximately 10% of patients with T1 colorectal carcinoma (8,9). In the clinical guidelines of the Japanese Society for Cancer of the Colon and Rectum (JSCCR), patients who undergo endoscopic resection for T1 colorectal carcinoma are considered to be at extremely low risk of developing lymph node metastasis if they have negative vertical margins, well or moderately differentiated adenocarcinoma, absence of vascular or lymphatic invasion, grade 0 or 1 tumor budding and submucosal invasion <1,000 µm (2).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced anus-preserving low anterior resection and intersphincteric resection have become more common as treatments for lower rectal carcinoma that avoid colostomies (21). However, some anal function disorders and complications have been reported following such resections, reducing patient quality of life (8). Due to similar rates of lymph node metastasis in patients with colon and rectal T1 carcinoma, surgical indications following endoscopic resection should be similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation